2003
DOI: 10.1021/jm020204l
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic Agents. 487. Synthesis and Biological Evaluation of the Antineoplastic Agent 3,4-Methylenedioxy-5,4‘-dimethoxy-3‘-amino-Z-stilbene and Derived Amino Acid Amides

Abstract: An efficient synthesis of 3,4-methylenedioxy-5,4'-dimethoxy-3'-amino-Z-stilbene (1c) and hydrochloride (1d) is reported. The nitrostilbene intermediate 6a was obtained via a Wittig reaction using phosphonium salt 4 and 3-nitro-4-methoxybenzaldehyde 5. A one-step reduction using zinc in acetic acid produced the synthetic objective amine 1c. The coupling of this amine with various Fmoc amino acids, followed by cleavage of the alpha-amine protecting group, resulted in a series of new cancer cell growth inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 19 publications
4
39
0
Order By: Relevance
“…Compound 9 also showed a potent inhibition of tubulin polymerization. Compounds 10 and 11 are under further development [52].…”
Section: Combretastatinsmentioning
confidence: 99%
“…Compound 9 also showed a potent inhibition of tubulin polymerization. Compounds 10 and 11 are under further development [52].…”
Section: Combretastatinsmentioning
confidence: 99%
“…Due to its structural simplicity, ease of synthesis, and potent antitumor activity, this class of molecules is widely studied to find potent anticancer agents. [11][12][13] Recently, conjugates bearing imidazo [2,1-b]thiazole scaffolds have become of interest due to their broad spectrum of pharmacological activities, such as antifungal, [14,15] antibacterial, [16][17][18] anti-inflammatory, [19] and antihypertensive properties. [20] It has been reported that they possess antitumor properties against a variety of human cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The most important intermediates for several biologically active molecules [56,57], fluoro compounds [58] have been synthesized through Wittig reaction.…”
Section: Wittig Reactionsmentioning
confidence: 99%